Behavioural Finance in Nepalgunj: Investor’s Decisions - Pokhrel, Lal Mani (Academia Research Journal, 2025)
The purpose of this study is to investigate the behavioural aspects influencing the investment decisions of personal investors in Nepali Gunj SubMetropolitan City, Nepal. Behavioural finance combines psychological viewpoints to explain how emotions, cognitive biases, and social influences affect financial decisions, while conventional finance assumes investors behave rationally. Using a quantitative research approach, the study investigates how psychological variables, social contacts, information availability, company reputation, and government rules influence investment behaviour. Descriptive statistics, Pearson’s correlation, and multiple linear regression were used to evaluate the findings of structured questionnaires with a 5-point Likert scale. According to research, firm reputation and access to trustworthy information, as well as psychological biases like loss aversion and overconfidence, greatly influence investment decisions. Contrary to earlier results on herding behaviour, social contacts had no statistically significant effect, while regulatory policies had a modest impact. The research highlights how crucial investor education, better regulatory openness, and fintech-based solutions are for lessening the negative consequences of cognitive biases. It also suggests more study on demographic differences and long-term market behaviour analysis. This research, which fills a need in the literature on behavioural finance in the Nepalese setting, particularly in smaller cities, provides important implications for investors, financial institutions, and politicians trying to encourage responsible and resilient investing practices.